INTERPROFESSIONAL EDUCATION MODEL FOR SPORT SECURITY PROFESSIONALS IN TURKEY - Ibrahim Mil, Halil; Sanli, Savas; Yildirim, Ali; Domac, Sezer (European Scientific Journal, ESJ, 2015)
Sport Security Professionals are entrsuted with maintaining peace, security and protecting human rights and freedoms in the sport areas. In pursuance of this, security agencies and professionals are to prevent crime and fight against it in cooperation and coordination with both local and international – level security agencies. To achieve this, they need practical training rather than theoretical one in not only prevocational training, but also in on- the- job training. In this study, it is recommended to apply interprofessional educational method commonly used in health science to training of the security professional in security science. In this context, it is pointed out how to apply interprofessional education model to prevocational formal education and on-the-job training of security professionals in sport security.